Super-zincophilic additive induced interphase modulation enables long-life Zn anodes at high current density and areal capacity. Issue 18 (11th April 2022) - Geng, Yaheng; Miao, Licheng; Yan, Zichao; Xin, Wenli; Zhang, Lei; Peng, Huiling; Li, Junwei; Zhu, Zhiqiang
Abstract : Super-zincophilic di-2-picolylamine has been developed as an effective electrolyte additive to modulate the Zn anode/electrolyte interphase, which enables reversible Zn plating/stripping even under severe cycling conditions. Abstract : Electrolyte additives have been widely used to enhance the reversibility of Zn plating/stripping in aqueous electrolyte, but limited improvements have been made at high current density and areal capacity. Here, super-zincophilic di-2-picolylamine (DPA) has been developed as an effective additive to enable long-life Zn anodes under severe cycling conditions. The DPA molecule, owing to its super-strong affinity to both Zn and Zn 2+, can preferentially adsorb on the Zn surface, which not only retards water adsorption but also powerfully regulates random Zn 2+ diffusion, thus stabilizing the anode/electrolyte interphase and eventually realizing highly reversible Zn plating/stripping even under high-current conditions. Remarkably, only trace amounts of the DPA additive (1 μL mL −1 ) enable the Zn‖Zn cell to deliver a lifespan of 1945 h at 10 mA cm −2 and 10 mA h cm −2, far surpassing the previously reported values. The Zn‖polyaniline full cell also demonstrates improved performance with the DPA additive. Our work provides new insights into developing dendrite-free Zn anodes for high-power aqueous batteries.